The association between psychotic experiences and disability: results from the WHO World Mental Health Surveys. (25th May 2017) - Navarro‐Mateu, F.; Alonso, J.; Lim, C. C. W.; Saha, S.; Aguilar‐Gaxiola, S.; Al‐Hamzawi, A.; Andrade, L. H.; Bromet, E. J.; Bruffaerts, R.; Chatterji, S.; Degenhardt, L.; de Girolamo, G.; et al.
Abstract : Objective: While psychotic experiences (PEs) are known to be associated with a range of mental and general medical disorders, little is known about the association between PEs and measures of disability. We aimed to investigate this question using the World Mental Health surveys. Method: Lifetime occurrences of six types of PEs were assessed along with 21 mental disorders and 14 general medical conditions. Disability was assessed with a modified version of the WHO Disability Assessment Schedule. Descriptive statistics and logistic regression models were used to investigate the association between PEs and high disability scores (top quartile) with various adjustments. Results: Respondents with PEs were more likely to have top quartile scores on global disability than respondents without PEs (19.1% vs. 7.5%; χ 2 = 190.1, P < 0.001) as well as greater likelihood of cognitive, social, and role impairment. Relationships persisted in each adjusted model. A significant dose–response relationship was also found for the PE type measures with most of these outcomes. Conclusions: Psychotic experiences are associated with disability measures with a dose–response relationship. These results are consistent with the view that PEs are associated with disability regardless of the presence of comorbid mental or general medical disorders.